2018
DOI: 10.1038/s41467-018-07708-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial fine-mapping for gene-by-environment effects identifies risk hot spots for schizophrenia

Abstract: Spatial mapping is a promising strategy to investigate the mechanisms underlying the incidence of psychosis. We analyzed a case-cohort study (n = 24,028), drawn from the 1.47 million Danish persons born between 1981 and 2005, using a novel framework for decomposing the geospatial risk for schizophrenia based on locale of upbringing and polygenic scores. Upbringing in a high environmental risk locale increases the risk for schizophrenia by 122%. Individuals living in a high gene-by-environmental risk locale hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This observation is in agreement with previous studies indicating that familial loading for mental illness and environmental risk factors for psychosis (i.e., urbanicity, social disadvantage, childhood adversity, cannabis use) may act in synergy to increase disease liability [46,51,[67][68][69][70]. Moreover, population-wide analyses underscore the contribution of upbringing locale, likely related with European Psychiatry socioeconomic profile, to psychosis manifestation and the modifiable role of genetic liability in the incidence of psychotic disorders [71]. We observed that individuals with presumably higher genetic risk for psychosis and growing up in families of lower SES could be more vulnerable to social maladjustment in childhood.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in agreement with previous studies indicating that familial loading for mental illness and environmental risk factors for psychosis (i.e., urbanicity, social disadvantage, childhood adversity, cannabis use) may act in synergy to increase disease liability [46,51,[67][68][69][70]. Moreover, population-wide analyses underscore the contribution of upbringing locale, likely related with European Psychiatry socioeconomic profile, to psychosis manifestation and the modifiable role of genetic liability in the incidence of psychotic disorders [71]. We observed that individuals with presumably higher genetic risk for psychosis and growing up in families of lower SES could be more vulnerable to social maladjustment in childhood.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, studies based on Danish registers have found that urbanicity of the place of birth and longer duration of being raised in urban settings both contributed to a higher risk of schizophrenia (Pedersen, 2015;Pedersen and Mortensen, 2006b;Vassos et al, 2012Vassos et al, , 2016. More recent population-based studies have found that individuals with higher polygenic risk scores related to risk of schizophrenia (but without the clinical diagnosis) are more likely to live in more densely populated settings (Engemann et al, 2020;Fan et al, 2018;Paksarian et al, 2018). However, this effect is relatively small, and it is not sufficient to explain the association between the urbanicity and risk of schizophrenia (Plana-Ripoll et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen dioxide concentrations vary geographically, with the highest levels in cities, major transport corridors, and coastal land areas near international shipping routes. 21 Individuals with higher genetic loading for schizophrenia tend to live in more densely urbanized areas, 7,22,23 possibly owing to intergenerational and intragenerational migration. Although this gene-environment correlation cannot explain the urban residence and later risk of schizophrenia, 23,24 it highlights the utility of the polygenic risk score in helping to identify novel risk factors.…”
Section: Introductionmentioning
confidence: 99%